Gereja Online: Studi Kasus HKBP Maranatha Cilegon dalam Membangun Gereja Online - Manalu, Musdodi Frans Jaswin (Indonesian Journal of Theology, 2024)
This study examines the development of online church amid the challenges faced by Huria Kristen Batak Protestan (HKBP) Maranatha Cilegon in constructing a physical or offline church due to local restrictions. As a case study, it investigates the establishment of online church as an alternative measure to the rejection of building non-Muslim houses of worship in Cilegon, Banten. Employing qualitative methods with data triangulation, this study explores the potential of online churches to serve the mission of the Church in the digital era and discusses the theological and practical implications of online worship spaces as sacred places in the post-pandemic context. By analyzing HKBP documents, related literature, and news sources, this study finds online church can be a viable alternative, supported by the Toba Batak principle of manjujung baringinna (“self-reliance”) that underscores the HKBP ethos. Despite theological challenges, such as the debate over online communion, the findings suggest that digital innovation can strengthen the faith of congregants facing physical and logistical challenges, helping them to overcome access barriers to worship and offering new opportunities to enhance the reach of church services in the digital age—all while maintaining the essence of Christian teachings and values.